An Object in its Own Domain: How Hispano New Mexican santos Are Situated In Space - Rosenstein, Carole (Ethnologies, 2002)
RésuméThis article characterizes Hispano New Mexican images of saints (santos) as powerful mediators of difference whose potency in that capacity transcends the interethnic sacred, civic, art world and market contexts in which they move. Describing how santos are invested with the power to encompass disparate forms drawn into a powerful halo a santo generates beyond its own embodiment, I argue that this “situation in space” not only makes santos resistant to being defined within broader spatial arrangements such as the “center”, “stage” and “boundary”, but that it actually works to redefine these larger spaces in the santos’ own terms. Because they can be altered, relocated and reclaimed in ways that large spaces cannot, objects that carry such a “spatial situatedness” should be recognized as part of the repertoire of cultural practices of resistance, prime semiotic vehicles for participants to use in contexts where claims to place, authority and autonomy are made through assertions about, contests over, and negotiations of space.